2018
DOI: 10.1155/2018/5319528
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Semipurified Fractions Isolated from Quercus infectoria on Bone Metabolism by Using hFOB 1.19 Human Fetal Osteoblast Cell Model

Abstract: Background. Quercus infectoria (QI) is a plant used in traditional medicines in Asia. The plant was reported to contain various active phytochemical compounds that have potential to stimulate bone formation. However, the precise mechanism of the stimulation effect of QI on osteoblast has not been elucidated. The present study was carried out to isolate QI semipurified fractions from aqueous QI extract and to delineate the molecular mechanism of QI semipurified fraction that enhanced bone formation by using hFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Pyrogallol is known to be associated with many biological activities and implicated in many anti-microbial activities such as anti-bacterial, anti-candidicidal and anti-fungicidal (43). Interestingly, Abdullah et al (44) recently revealed that different semi purifed fractions of the aqueous extract of Q. infectoria have similar polyphenolic compositions such as gallic acid and digallate as well as ellagic acid, syringic acid and theogallin, which have also been detected using liquid chromatography mass spectrometry (LC-MS), implying the richness of phenolic compounds in the galls. Similarly, ethanol extract of Q. infectoria galls has also been shown for their high content of phenolic compounds such as p-Hydroxybenzoic, pyrogallol, catechol, caffeine and gallic acid (31).…”
Section: Resultsmentioning
confidence: 99%
“…Pyrogallol is known to be associated with many biological activities and implicated in many anti-microbial activities such as anti-bacterial, anti-candidicidal and anti-fungicidal (43). Interestingly, Abdullah et al (44) recently revealed that different semi purifed fractions of the aqueous extract of Q. infectoria have similar polyphenolic compositions such as gallic acid and digallate as well as ellagic acid, syringic acid and theogallin, which have also been detected using liquid chromatography mass spectrometry (LC-MS), implying the richness of phenolic compounds in the galls. Similarly, ethanol extract of Q. infectoria galls has also been shown for their high content of phenolic compounds such as p-Hydroxybenzoic, pyrogallol, catechol, caffeine and gallic acid (31).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of phenolic compounds in QIG has been extensively quantified, with 50%-70% polyphenols as principal compounds [39] . This kind of water-soluble components is obviously the most in the aqueous extract, but in this anti CRC activity test, the ethanol extract of QIG shows the strongest effect.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of phenolic compounds in Q. infectoria galls have been extensively quantified, with 50%–70% tannic acid, gallic acid and ellagic acid as principal constituents ( 7 , 40 ). Among these phenolic compounds, ellagic acid has been widely studied exhibiting promising antimalarial activities against P. falciparum in vitro ( 41 ), P. vinckei in vivo ( 41 ), P. yeolli in vivo ( 42 ) and P. berghei in vivo ( 43 ) without any toxicity ( 42 ).…”
Section: Discussionmentioning
confidence: 99%